Positive contact and empathy as predictors of primary care providers’ willingness to prescribe medications for opioid use disorder - Lindsay Y. Dhanani; William C. Miller; O. Trent Hall; Daniel L. Brook; Janet E. Simon; Vivian Go; Berkeley Franz (SSM - Mental Health, 2023)
Introduction: Patients with opioid use disorder (OUD) have a heightened need for quality health care, including access to evidence-based medications to reduce cravings and prevent overdose. However, primary care providers (PCPs) are reluctant to work with patients with OUD and implement medication prescribing into primary care practice. Previous studies have sought to identify potential ways to overcome these barriers, but often utilize interventions that facilitate both positive contact with as well as empathy for patients with OUD. In this study, we jointly assess positive contact and empathy to determine their unique impact on treatment attitudes and behaviors among PCPs, after controlling for other known predictors. Methods: We surveyed 409 PCPs currently practicing in Ohio in 2022. Our primary dependent variables were willingness to work with patients with OUD, receipt of an X-waiver to prescribe buprenorphine, and interest in receiving an X-waiver. Our primary independent variables were positive contact and empathy toward patients with OUD. We computed bivariate correlations and multivariable linear regression (for continuous dependent variables) and logistic regression (for binary dependent variables) to understand the relationship between positive contact, empathy, and our outcome variables while accounting for other known predictors and relevant participant demographics. Results: Positive contact was positively correlated with willingness to work with patients with OUD, receipt of the X-waiver, an interest in receiving the X-waiver, more frequent checking with patients about the need for naloxone, and higher odds of naloxone prescribing. These relationships held after accounting for PCP demographics, explicit bias toward patients with OUD, and overall levels of contact with patients with OUD. Empathy, conversely, was not a significant predictor of any treatment outcomes in the fully adjusted models. Conclusion: Interventions and medical education programs aimed at improving treatment outcomes for patients with OUD should facilitate positive contact between PCPs and patients with OUD.